Estrogen bioassy of Pueraria mirifica Airy Shaw & Suvatabandhu - Siangcham T. (2014)
Pueraria mirifica Airy Shaw & Suvatabandhu has been used by Thai women for centuries as a rejuvenating herb. The scientific claim for its phytoestrogenic property leads to the popular use of this plant in several herbal formulations. This research project was carried out to examine estrogenic activity of P. mirifica from Lampang Province, Thailand, one of the areas that it is harvested for using as raw material in herbal industries. Estrogen bioassay of aqueous extract from P. mirifica at concentrations of 0.1 and 0.2 g/ml was performed in immature ovariectomized mice in comparison to both the negative and positive control groups. Vaginal orifice of mice treated with the extract in all groups and with the positive control group which injected with estradiol benzoate (EB) opened earlier than the negative control mice and vaginal cornification was also found in these 3 groups only. Moreover, the extract significantly increased uterine weight and uterine epithelium height as compared to negative control group with the comparable degree of increment to those of EB treated group. The data of this present study indicated that dried powder of P. mirifica which is used as raw material for herbal products of Lampang Province, exhibited the potent estrogenic activity. © 2010 Academic Journals.